Apparent survival and return rate of breeders in the southern temperate White-rumped Swallow Tachycineta leucorrhoa - Bulit, Florencia (2011)
Life-histories and demographic parameters of southern temperate bird species have been little studied. We estimated return rates between years and sexes, and adult apparent survival and recapture probabilities with mark-recapture data on White-rumped Swallows and found a lower return rate of unsuccessful females. There was little support for influences of sex or year on survival rates. The estimates were equivalent to the lowest value reported for a northern congener, in contrast to the prediction of geographical variation under life-history theory.